Exploring the Performance Impact of Multi Protocol LABEL Switching Network over Conventional IP Network on the basis of Voice and TEXT - Swati Srivastava, Akhilesh Kumar Singh, Juginder Pal Singh (International Journal of Advanced Science and Technology, 2020)
Multi protocol Label Switching (MPLS) is considered to be latest technology to improve the speed performance and efficiency of network along with its QoS (Service Quality for congestion of network) and their scalability. The research article proposed here the benefits of multi protocol label switching to the traditional data network on the concept of ns2 simulator. This switching is basically used for combining the best features of Layer 3 along with Layer 2 of Open System Interconnection model of the network. In this switching the packets are transmitted on the basis of label. Multi protocol Label Switching also facilitates the quick rerouting technique and traffic reengineering. This research article proposes that Multi protocol Label Switching behaves much matured and performs much efficiently than traditional switching when tested on some important parameters.